# How do you solve #5/( y - 2) = y+2#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 5/(y - 2) = y + 2, you can start by multiplying both sides of the equation by (y - 2) to eliminate the denominator. This gives you 5 = (y + 2)(y - 2). Expanding the right side of the equation, you get 5 = y^2 - 4. Rearranging the equation, you have y^2 - 4 - 5 = 0, which simplifies to y^2 - 9 = 0. Factoring the quadratic equation, you have (y - 3)(y + 3) = 0. Setting each factor equal to zero, you find y = 3 or y = -3. Therefore, the solutions to the equation are y = 3 and y = -3.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7